Proverbs in the Qur'an from the Perspective of Islamic Education - Muh. Luqmanul Hakim (al-Afkar, Journal For Islamic Studies, 2025)
Amtsal al-Qur'an is a very effective method in making it easier for students to understand the learning materials provided by educators. Amtsal is also very important for visualizing something that is still abstract so that it becomes something that looks real. The proverbs in the Koran are stated in various sentences, so deeper knowledge is needed to understand them. This type of research uses library research or library research. For data collection techniques, researchers used documentation techniques. The data analysis technique that researchers use is the content analysis technique. The results of this research show that the Qur'an focuses its education on humans, placing it in harmony with the elements of creation, namely body, mind and soul. Therefore, the educational materials presented almost always lead to the education of the human soul, mind and body itself. Therefore, the process of delivering material in learning activities will be more interesting and efficient if the material is packaged using stories and parables, of course, this is based on the human instinct or tendency to really like parables.